Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3389/fimmu.2016.00381
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Enriched Environment on Murine T Cell Differentiation and Gene Expression Profile

Abstract: T cells are known to be plastic and to change their phenotype according to the cellular and biochemical milieu they are embedded in. In this study, we transposed this concept at a macroscopic level assessing whether changes in the environmental housing conditions of C57/BL6 mice would influence the phenotype and function of T cells. Our study shows that exposure to 2 weeks in an enriched environment (EE) does not impact the T cell repertoire in vivo and causes no changes in the early TCR-driven activation even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 82 publications
(63 reference statements)
0
11
1
Order By: Relevance
“…Anti-tumor activity of an EE has been shown in different cancers ( Cao et al, 2010 ; Nachat-Kappes et al, 2012 ; Garofalo et al, 2015 ), even if some results were not confirmed ( Westwood et al, 2013 ). Environmental stimuli also shape immune functions, modulating NK cells ( Garofalo et al, 2015 ; Song et al, 2017 ), T helper cells ( Rattazzi et al, 2016 ), and myeloid cells ( Chabry et al, 2015 ). NK cells exert anti-tumor function by direct cytotoxic activity, producing several cytokines, chemokines and growth factors ( Vivier et al, 2011 ; Guillerey and Smyth, 2016 ; Stabile et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Anti-tumor activity of an EE has been shown in different cancers ( Cao et al, 2010 ; Nachat-Kappes et al, 2012 ; Garofalo et al, 2015 ), even if some results were not confirmed ( Westwood et al, 2013 ). Environmental stimuli also shape immune functions, modulating NK cells ( Garofalo et al, 2015 ; Song et al, 2017 ), T helper cells ( Rattazzi et al, 2016 ), and myeloid cells ( Chabry et al, 2015 ). NK cells exert anti-tumor function by direct cytotoxic activity, producing several cytokines, chemokines and growth factors ( Vivier et al, 2011 ; Guillerey and Smyth, 2016 ; Stabile et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent publication reports that EE leads to a unique T helper effector cell phenotype upon differentiation in vitro featured by reduced production of IFN-γ although no in vivo impact was observed (37). In contrast, our in vivo data in naïve or EAE conditions demonstrated significant impact of EE on thymocyte differentiation and T cell repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, people with positive emotions showed lower susceptibility to infection ( 15 , 16 ) and greater immune response ( 17 , 18 ). This role of “immune enhancer” is mediated by higher levels of antibodies ( 18 ) and T cells ( 19 21 ), and increased activity of natural killer (NK) cells ( 19 , 22 ), as well as reduced inflammatory markers including interleukin-6 (IL-6) and C-reactive protein (CRP) ( 22 , 23 ). In contrast, negative emotions (e.g., sadness, nervousness, worry, loneliness, and fear) and psychological stress are associated with poorer immunological function with lower NK cell cytotoxicity ( 8 ), fewer T cells ( 24 ), and increased inflammatory markers ( 25 ).…”
Section: Affective Immunologymentioning
confidence: 99%